Antioxidant Peel off Gel Mask with Stevia Rebaudiana Bert Extract - Lia Kusmita (Journal of Global Pharma Technology, 2019)
Anti-oxidant activity is the activity to deter free radicals. Stevia rebaudiana Bert contains multiple compounds, such as flavonoid, that are capable of deterring free radicals.  The aim of this research was to produce peel off gel mask based on Stevia rebaudiana Bert extract with anti-oxidant abilities. Additionally, it was also used to determine the characteristics including pH, viscosity, dispersion, adhesion, and drying time of the preparation. This research was initiated by creation of the extract, continued by creation of peel off gel mask formula, and finalized by testing the anti-oxidant properties. The research showed a result with the value of Stevia rebaudiana Bert extract (IC50 = 60 µg/ ml). From the evaluation result of anti-oxidant activity from the peel of mask using Stevia rebaudiana Bert extract, it was proven that the higher the extract’s concentration, the smaller the IC50 value, which indicated higher anti-oxidant activity. The characteristic evaluation result of all formula showed that the characteristic evaluation value still fulfilled the set criteria to produced good peel off gel mask. Keywords: Stevia rebaudiana Bert; anti-oxidant; peel off gel mask